A New Full-Rate Full-Diversity Space-Time Block Code With Nonvanishing Determinants and Simplified Maximum-Likelihood Decoding - Paredes, J.M.; Gershman, A.B.; Gharavi-Alkhansari, M. (IEEE transactions on signal processing, 2008)
A new 2times2 full-rate full-diversity linear dispersion space-time block code (STBC) is designed by augmenting the generator of the lattice of the Alamouti's orthogonal STBC and optimizing it according to the criterion of the maximal worst codeword difference determinant. The proposed STBC is proved to satisfy the nonvanishing determinant property and, therefore, to achieve the optimal diversity-multiplexing gain (DMG) tradeoff, while offering a reduced computational complexity of maximum- likelihood (ML) decoding as compared to other existing full-rate STBCs. The performance of our new code is shown to be comparable to that of the best full-rate STBCs known so far.